2006
DOI: 10.1097/01.bpo.0000229974.78565.cc
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Adolescent Lumbar Disk Herniation

Abstract: The authors have retrospectively studied the trends in etiology, symptoms, and rate of recurrence for adolescents with disk herniations to determine the age at onset of symptoms, mechanism of injury, familial history, pattern of symptoms, level of herniation, method of treatment, and rate of recurrence. The review revealed a higher incidence of adolescent lumbar disk herniations in female patients and a higher percentage of patients with a family history than previously reported. Leg pain continues to be the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 8 publications
1
11
0
1
Order By: Relevance
“…Varlotta et al 22 found that in adolescent patients with disc herniation that a larger proportion of individuals had a positive family history of disc herniation than in control subjects. This finding was subsequently further supported by other investigators, such as Frino et al 23 reports of the Finnish Twin Study, cigarette smoking status was found to greatly increase the ability of predicting LDD. 33 .…”
Section: Genetic Component Of Lumbar Disc Degenerationsupporting
confidence: 74%
“…Varlotta et al 22 found that in adolescent patients with disc herniation that a larger proportion of individuals had a positive family history of disc herniation than in control subjects. This finding was subsequently further supported by other investigators, such as Frino et al 23 reports of the Finnish Twin Study, cigarette smoking status was found to greatly increase the ability of predicting LDD. 33 .…”
Section: Genetic Component Of Lumbar Disc Degenerationsupporting
confidence: 74%
“…The first descriptions of familial predisposition for lumbar IDD were found in juvenile and adolescent populations (103)(104)(105)(106). The study of juvenile lumbar disc herniation is especially interesting since in young patients, normal disc aging and risk factors such as occupation, smoking and comorbidities have little, if any, influence on disease predisposition.…”
Section: Familial Predisposition and Heritability Estimationmentioning
confidence: 99%
“…Post-operative infection, e.g. wound infection and discitis secondary to lumbar spine surgery is rare in children and adolescents with only few cases being reported in the literature [15,46,67]. Although there have been reports of narrowing of disc space, foraminal stenosis and adjacent disc degeneration from few months to several years after discectomy, the clinical outcome was not affected accordingly [46,49,60,63].…”
Section: Post-operative Complicationsmentioning
confidence: 99%